A multi-purpose force-controlled loading device for cartilage and meniscus functionality assessment using advanced MRI techniques - Truhn, Daniel; Brill, Nicolai; Braun, Benedikt; Merhof, Dorit; Kuhl, Christiane; Knobe, Matthias; Thuering, Johannes; Nebelung, Sven (Journal of the Mechanical Behavior of Biomedical Materials, 2020)
Response to loading of soft tissues as assessed by advanced magnetic resonance imaging (MRI) techniques is a promising approach to evaluate tissue functionality beyond (statically obtained) structural and compositional features. As cartilage and meniscus pathologies are closely intertwined in osteoarthritis (OA) and beyond, both tissues should ideally be studied to elucidate further the underlying mechanisms involved in load transmission and its failure leading to OA. Hence, we devised, constructed and validated a dedicated MRI-compatible pneumatic force-controlled loading device to study cartilage and meniscus functionality in a standardized and reproducible manner and in reference to alternative tissue evaluation methods. Mechanical reference measurements using digital force sensors confirmed the reproducible application of forces in the range of 0–76N. To demonstrate the device's utility in a basic research context, MRI measurements of human articular cartilage (obtained from the lateral femoral condyle, n = 5) and meniscus (obtained from lateral meniscus body, n = 5) were performed in the unloaded (δ0) and loaded configurations (δ1: [cartilage] 0.75 bar corresponding to 15.1 N, [meniscus] 2 bar corresponding to 37.1 N; δ2: [cartilage] 1.5 bar corresponding to 28.6 N, [meniscus] 4 bar corresponding to 69.1 N). Cartilage samples were directly indented, while meniscus samples were subject to torque-induced compression using a dedicated lever compression device. Morphological MR Imaging using Proton Density-weighted sequences and quantitative MR Imaging using T2 and T1ρ mapping were performed serially and at high resolution. For reference, samples underwent subsequent biomechanical and histological reference evaluation. In conclusion, the force-controlled loading device has been validated for the non-invasive response-to-loading assessment of human cartilage and meniscus samples by advanced MRI techniques. Hereby, both tissues may be functionally evaluated in combination, beyond mere static analysis and in reference to histological and biomechanical measures.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Cartilage; Loading; Meniscus; MRI; Osteoarthritis